2009
DOI: 10.1029/2009jb006548
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of fluid‐driven fracture growth in naturally fractured reservoirs with simple network geometries

Abstract: [1] A numerical model has been developed for fluid-driven opening mode fracture growth in a naturally fractured formation. The rock formation contains discrete deformable fractures, which are initially closed but conductive because of their preexisting apertures. Fluid flow that develops along fractures depends on fracture geometry defined by preexisting aperture distribution, offsets along a fracture path, and intersections of two or more fractures. The model couples fluid flow, elastic deformation, and frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 62 publications
(120 reference statements)
0
82
0
Order By: Relevance
“…The existing numerical models for extracting geothermal energy are almost all based on the continuum approach (Hunsweck et al, 2013;Secchi and Schrefler, 2012;Zhang et al, 2009). Although these models have been shown to be valuable in geothermal energy exploration, as reported in a number of case studies in the literature (Zhou and Hou, 2013;Gong et al, 2011;Blocher et al, 2010;Bataille et al, 2006), they are incapable of capturing the full physics of the modeled fractured rocks.…”
Section: Discussionmentioning
confidence: 97%
“…The existing numerical models for extracting geothermal energy are almost all based on the continuum approach (Hunsweck et al, 2013;Secchi and Schrefler, 2012;Zhang et al, 2009). Although these models have been shown to be valuable in geothermal energy exploration, as reported in a number of case studies in the literature (Zhou and Hou, 2013;Gong et al, 2011;Blocher et al, 2010;Bataille et al, 2006), they are incapable of capturing the full physics of the modeled fractured rocks.…”
Section: Discussionmentioning
confidence: 97%
“…In this case, the propagation of shear slip is driven by the slip-weakened friction force, and by the fast fluid pressure diffusion in the fracture [27][28][29]. Shear-induced dilation enhances fracture conductivity and accelerates the pressure diffusion in fracture, which in turn transmits the reduced shear force in the slipped part of the fracture toward the not-yet-slipped part of the fracture ahead of the slip front, causing the slip front to propagate.…”
Section: Theoretical Developmentmentioning
confidence: 96%
“…The large separation between these curves indicates that fracture crossing is very sensitive to the intersection angle. Laboratory testing [27][28][29][30], to be described in Chapter 9, has been carried out for verifying the above crossing criterion. The predictions from the above extended Renshaw and Pollard crossing criterion are in good agreement with the results from laboratory testing.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Khristianovich and Zheltov (1955) recognized that stable crack growth is associated with the existence of an unpressurized cavity or a lag zone arising from the coupling between factors that generate the net pressure distribution in the fracture, the compressive confining stress, and the fracture toughness of the rock. A numerical scheme with implicit iterations for tracking the fluid fronts has been described by Zhang et al (2005Zhang et al ( , 2009 and the reader is referred to those papers for more details. It was found that these moving boundaries can be approximated by using our numerical method (Zhang et al, 2005(Zhang et al, , 2009).…”
Section: Fluid Flow Along the Fracturementioning
confidence: 99%
“…A numerical scheme with implicit iterations for tracking the fluid fronts has been described by Zhang et al (2005Zhang et al ( , 2009 and the reader is referred to those papers for more details. It was found that these moving boundaries can be approximated by using our numerical method (Zhang et al, 2005(Zhang et al, , 2009). …”
Section: Fluid Flow Along the Fracturementioning
confidence: 99%